Traditional knowledge of temuan tribe on medicinal plant used. Case study: Kampung Orang Asli Panson, Hulu Langat, Selangor - Maznah Muning; M.A.M. Arshad; Z. Ismail; A.H. Gerten (Faculty of Science and Natural Resources, 2020)
The purpose of this study was to document traditional knowledge on medicinal plants, of the Temuan tribe from Kampung Orang Asli Panson, Hulu Langat, Selangor. This study is based on information obtained through direct observation and interviews with knowledgeable villagers. A total of 25 species of medicinal plants used for treating various ailments were recorded. 39% of the species were used by using the root part, 26% were used by the leaves part of the species, 13% by the rhizome parts, 10% by the fruits parts and 6% respectively by using the tips and stem parts of the species.